Konsep Integrasi Pembangkit Berbasis Energi Terbarukan Sebagai Sistem Mikrogrid Di Kabupaten Pesisir Selatan - Rauf, Rosnita (Jurusan Teknik Elektro Universitas Andalas, 2013)
Energy grid management systems are the future of many developed countries today was developed called smart grid. Energy management in a smart grid is to use the concept of merging a few plants and a group of users in a particular area or within a certain grid. Generating an initial variable as the giver of energy input while the end users are variable power grid as a user of this hybrid energi. Sistem simulated using HOMER program and perform calculations with MATLAB system. Integration of these variables in a management area network will provide the optimal parameter if it can be supported by computer networks to obtain communications data from the SCADA system. With mikrogrid designed to have two streams, namely electricity and information flow, SCADA here designed to cover all the flow of information from the plant to the customer. The basic activity is the activity under taken monitoring and control of activities which aim to balance the grid. Monitoring aims to add to the data on plants and customers in order to assist decision-making at the micro grid system inside. Control activities aim to maintain a balanced energy intake of multiple power plant priority points toward energy use by multiple end users in the grid.Keywords: Energy, Mikrogrid, HOMER, MATLAB, SCADA AbstrakSistem pengelolaan grid energi masa depan yang banyak dikembangkan negara maju saat ini biasa disebut smart grid. Pengelolaan energi dalam smart grid ini menggunakan konsep penggabungan beberapa pembangkit dan sekelompok pengguna dalam wilayah tertentu atau dalam grid tertentu. Pembangkit merupakan variabel awal sebagai pemberi masukan energi sedangkan pengguna merupakan variabel akhir grid sebagai pemakai energi. Sistem tenaga hybrid ini disimulasikan dengan menggunakan program HOMER dan melakukan perhitungan system dengan MATLAB. Penggabungan variabel-variabel tersebut dalam sebuah area network akan memberikan pengelolaan parameter yang optimal jika dapat didukung dengan jaringan computer untuk mendapatkan komunikasi data dari system SCADA. Dengan mikrogrid dirancang mempunyai dua aliran yaitu aliran listrik dan aliran informasi, SCADA disini dirancang untuk mencakup semua aliran informasi dari pembangkit hingga pelanggan. Aktivitas dasar yang dilakukan adalah aktivitas monitoring dan aktivitas kendali yang bertujuan untuk keseimbangan grid. Monitoring bertujuan untuk menambah data pada pembangkit dan pelanggan sehingga dapat membantu pengambilan keputusan pada mikro system didalam grid. Aktivitas pengendalian bertujuan untuk menjaga pengasupan energi yang seimbang dari multiple power plant menuju titik-titik prioritas penggunaan energi oleh multiple end user didalam grid. Keywords: Energy, Mikrogrid, HOMER, MATLAB, SCADA